Critical pedagogy an exploration of contemporary themes and issues - Boronski, Tomas (Routledge, Taylor & Francis Group, 2022)
"This accessible text provides a clear overview of the contemporary themes and challenges within critical pedagogy, and suggests a path towards a more conscientious world for all through education. Boronski encourages us to imagine radical alternatives to current approaches, not merely for ideological reasons, but due to increasing necessity for environmental and sociological perspectives. With case studies, discussion tasks and exemplars from global history woven throughout, each chapter considers a prominent societal and educational issue, tackling some difficult and unsettling areas. Embedded in this exploration is an understanding and application of key concepts, such as justice, equality, rights and power, and how these relate to a range of topics in UK schooling. These include the role of teachers in an age of hyper surveillance and performance monitoring, alternative approaches to education, and the growing fear of the 'other'. Essential reading for Education Studies students at undergraduate and Master's level, this comprehensive text will also be of interest to students of Social Policy, Sociology and Politics programmes"--